P175 Complete endoscopic healing is associated with lower disability than partial mucosal healing in Crohn's disease: a prospective multicentric study. (27th May 2021) - Yzet, C; Brazier, F; Sebbagh, V; Vanelslander, P; Dejour, V; David, B; Nguyen-Khac, E; Diouf, M; Fumery, M
Abstract: Background: Crohn's disease (CD) has a significant impact on health status and quality of life, by affecting physical and emotional well-being and by impairment of social and functional abilities. In the era of treat to target concept, endoscopic healing has emerged to be the goal to achieve to prevent intestinal damage and disability. It is not clear what level of endoscopic healing is associated with CD disability. We, therefore, aimed to compare disability associated to complete endoscopic healing or partial endoscopic healing in patients with CD. Methods: We conducted a multicentric prospective study, between September 2019 and November 2020, in one University Hospital, one general hospital and one private practice center including consecutive patients with CD in clinical remission and either complete mucosal healing (CDEIS =0) or partial mucosal healing (CDEIS > 0 and ≤ 4). The 10-item self-questionnaire IBD-disk was used to assess disability. Moderate-to-severe disability was defined as an overall IBD-disk score ≥ 40. Results: A total of 82 patients were included. Forty-four (53%) were women, the median age and disease duration were respectively 35.3 years (Interquartile range (IQR 28.6–45.2) and 8.0 years (IQR, 3.0–17.0). The median overall IBD-disk score was 26.5 (IQR, 9 -45.0) and 30 (36.6%) had moderate-to-severe disability. Complete endoscopic healing was observed in 48 patients (57.3%). Median IBD-Disk score was respectively 24 (IQR, 9.0–40.5) and 34 (IQR, 9.5–51.5) for patients with complete and partial endoscopic healing (p=0.068). Respectively, 13/48 (27%) and 17/34 (50%) of patients with complete and partial endoscopic healing had moderate-to-severe disability (p=0.039). In multivariate analysis, partial mucosal healing (OR=3.04, CI95% [1.11, 8.94], p=0.03), female gender (OR=3.93, CI95% [1.43, 11.94], p=0.008) and smoking (OR= CI95% 5.88 [1.72, 25.0] p=0.039) were significantly associated with moderate-to-severe disability. Among the IBD-disk subscores, defecation score (median, IQR) (0.0 [0.0–3.0] vs 4.0 [0.0–7.5], p=0.028) and energy score (4.0 [0.0–6.0] vs 6.0 [2.5–8.0], p=0.023) were significantly lower in complete endoscopic healing. Conclusion: One-third of patient with endoscopic healing reported moderate-to-severe disability. Complete endoscopic healing (CDEIS = 0) was associated with lower disability than partial endoscopic healing (CDEIS > 0 and ≤ 4) in CD. Deeper endoscopic healing may be needed to reduce the risk of disability in CD.